Actitudes hacia el aprendizaje y la contaminación ambiental en niños de la Institución Educativa Inicial Bilingüe Intercultural N° 386 Bellavista Callarú Loreto 2023 - Guerrero Coello, Lionza (2024)
The study aims to relate attitudes towards learning and environmental pollution among children from the Bilingual Intercultural Initial Educational Institution No. 386 Bellavista Callarú, Loreto 2023. The target population comprises 157 enrolled children in the school, who were observed using a previously validated guide by experts. The methodology employed is relational, field-based, bivariate, and cross sectional. The results reveal a significant correlation between attitudes towards learning and environmental pollution, supported by a p-value of 0.017, indicating a positive relationship between both variables. This finding suggests that children with more positive attitudes towards learning also demonstrate greater awareness and concern for the environment.